ANALYSIS OF ACCIDENTAL EVENTS AT THE RAIL CROSSING (Perner's Contacts, 2020)
The paper focuses on the issue of safety at level crossings, which are a very important element in rail transport. Statistics show that road accidents account for more than a quarter of all rail accidents in the EU. In addition to statistical indicators of accidents at railway crossings, the authors of the article had at their disposal detailed data on the tragic accident from 2009, where twelve people were killed, as well as other serious injuries. According to the analysis of the causes and course of the accident, it shows how important it is to use the most modern security elements at railway crossings, where it is not possible to pass road and rail traffic off-level.
Keywords: railway crossings; safety; accident; participants